Chapter 3: Citizenship Education: Rangatahi Electoral Participation - Tawhai, Veronica (Mana tangata politics of empowerment, 2011)
This is a collection of papers by senior Maori academics who are experts and have considerable mana in their chosen fields. The ten contributing authors, who are academics at Massey University, discuss the Maori language, marae, religion, the Treaty of Waitangi, the State and Maori, citizenship education, mental health, the health workforce, kaitiakitanga and horticulture. The book discusses Maori development and contemporary issues concerning Maori, both from the authors' perspectives and across different disciplines.
Keywords: elections; rangatahi; tiriti o waitangi/treaty of waitangi; voting

Always Speaking: The Treaty of Waitangi and Public Policy - Tawhai, Veronica; Gray-Sharp, Katarina (Huia Publishers, 2011)
This is a collection of papers that examine the current place of the Treaty of Waitangi in core public policy areas. The authors analyse the tensions and dynamics in the relationship between Maori and the Crown in their areas of expertise, detail the key challenges being faced, and provide insights on how these can be overcome. The policy areas covered in the collection span the environment, Maori and social development, health, broadcasting, the Maori language, prison and the courts, local government, research, science and technology, culture and heritage, foreign affairs, women's issues, labour, youth, education, economics, housing and the electoral system.
Keywords: civil Rights